Comparative Analysis Of Intensive And Traditional Beef Cattle Business Income In East Oku District - Septika Susanti; Munajat Munajat; Yunita Sari (International Journal of Economics, Business and Innovation Research, 2024)
Cattle farming is one of the resources to fulfill the need for food in the form of meat, which has high economic value and has many benefits in life. This research was conducted in East OKU District, precisely in Buay Madang Timur Subdistrict. The determination of the location was done intentionally (Purposive) with the consideration that Buay Madang Timur Subdistrict is the center of the cattle business in East OKU district and has the highest population and the largest number of breeders in the beef cattle business in South Sumatra Province. The research method used in this study was the case study method. According to Sriati (2014), the case study method is a research method used for the type of research where the research location chooses a special population (typical) compared to other research locations. Based on this study because the population was greater than 100 respondents, the authors took 25% of the population in the population, namely 35 respondents in the Research Sample of intensive beef cattle business and 34 samples of traditional beef cattle business. The methods of processing and analyzing data in this study were to answer the first problem formulation to compare income using income analysis, T-test, and Break Event Point. From the above research, the income of intensive cattle farming business amounted to Rp. 37. 965. 058, 53 / month while the traditional cattle farming business amounted to Rp. 33. 017. 401, 96 / month. semi-intensive cattle farming business income was greater than of traditional cattle farming business with a difference in income of Rp. 4. 945. 656, 57/month. Break-even Point analysis based on research for intensive farming of 3 heads and for traditional cattle farming of 2 heads, based on these results, beef cattle farming was feasible for both intensive and traditional farms. Based on the results of the t-test analysis in Table 4. 12 above obtained the results: at a confidence level of 95% and an error rate of 5% or a value of α = 0, 05 obtained that the t-count value = 15, 64 and the t-table value = 2, 018. The value of t-hit> t-table (15, 64 < 2, 018), indicated that Ha was accepted and Ho was rejected. The value of t-hit > t-table meant that there was a real (significant) difference between the average income of intensive and traditional cattle farming income in East OKU